A Web-Based Baby Health Record System - Farah Hamizah Suhaimi; Rozaida Ghazali (Applied Information Technology And Computer Science, 2023)
Babies and Children’s health record book (RKK book) is a child health record that keeps all the examination results conducted by medical staff to observe a baby‘s growth development. During the implementation of the manual record book record, some issues identified include its exposure to damage by natural disasters and its inefficient process of managing the record book. A system was developed by using a structured approach with prototype methodology to encounter issues faced by its users before. The potential users of the system were the administrator, medical staff, and baby guardians. HTML, PHP, CSS, and JavaScript were used for the system development. While the database record of the system will be kept in MySQL using the XAMPP server. Upon completion, it met most of the functions and requirements as planned, but there were still a few limitations identified to be improved in future works.